Social psychology - Brown, Carol, 1937-; Sage eBooks (London : SAGE, 2006)
Providing student readers with essential help for all aspects of social psychology, this text includes advice on revising for exams, preparing and writing course assessment materials, and enhancing and progressing their knowledge and skills in line with course requirements.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Social psychology; Electronic books